Benign Metastasizing Leiomyoma of the Uterus: Rare Manifestation of a Frequent Pathology - Maria Inês Raposo; Catarina Meireles; Mariana Cardoso; Mariana Ormonde; Cristina Ramalho; Mónica Pires; Mariana Afonso; Almerinda Petiz (Hindawi Limited, 2018)
Benign Metastasizing Leiomyoma (BML) is a rare condition with few cases reported in the literature. It is usually incidentally diagnosed several years after a primary gynecological surgery for uterine leiomyoma. Differential diagnosis of BML is complex requiring an extensive work-up and exclusion of malignancy. Here, we report two cases of BML based on similarity of histopathological, immunohistochemical, and genetic patterns between lung nodules and uterine leiomyoma previously resected, evidencing the variability of clinical and radiological features of BML. We highlight the importance of 19q and 22q deletions as highly suggestive of BML. These findings are particularly relevant when there is no uterine sample for review.